Other Militia Not to Parade, etc., ch. 24-Relating to the Militia, § 13 in Acts of the Legislature of West Virginia (1889) § 13. - (:unkn) unknown (My University, 1889)
The West Virginia National Guard shall consist of not exceeding twenty companies of infantry, which divided into regiments, shall constitute the West Virginia National Guard, and it shall not be lawful for anybody[sic] of men whatsoever, other than the regularly organized National Guard or militia or the troops of the United States, to associate themselves together as a military company or organization, or to parade in public with arms, in any city or town in the state, without the license of the governor therefor, which may at any time be revoked, nor shall it be lawful for any city or town to raise or appropriate any money towards arming, equipping, uniforming, or in any way supporting or sustaining or providing drill rooms or armories, for any such bodies of men.
Keywords: MILITIAS